If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -4 = x + -76 Reorder the terms: -4 + -2x = x + -76 Reorder the terms: -4 + -2x = -76 + x Solving -4 + -2x = -76 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + -2x + -1x = -76 + x + -1x Combine like terms: -2x + -1x = -3x -4 + -3x = -76 + x + -1x Combine like terms: x + -1x = 0 -4 + -3x = -76 + 0 -4 + -3x = -76 Add '4' to each side of the equation. -4 + 4 + -3x = -76 + 4 Combine like terms: -4 + 4 = 0 0 + -3x = -76 + 4 -3x = -76 + 4 Combine like terms: -76 + 4 = -72 -3x = -72 Divide each side by '-3'. x = 24 Simplifying x = 24
| 14+x+7x=-4+3x+2x | | 9x-2x=91 | | -5.5+0.56=-1 | | 11(-5.5)+9=4(-5.5)-30 | | -8x-6=9x-4 | | -8x-6=9x-4 | | 35-52.5=x | | x-104=9x-8 | | -16w=-64 | | -5(d-8)= | | a^3-b^4= | | 35x=52.5x-57.75 | | 7x^2-45x-20=0 | | 6.09+25=37.0881+5x | | 1x-2=2 | | 83-56= | | 4.5-3lnx=1.5 | | 11a+9=4a-30 | | log[2](4x)=long[2](6+x) | | y^3=125 | | g-9=-3.64 | | 2(5y+1)=-2(y-1)-48 | | 3x-y=12fory | | 11(3)+9=4(3)-30 | | -4x+7(-x+14)=197 | | -14+6b+7-2=1+5b | | s+2.52=19.49 | | 6x-7(6x-29)=-13 | | -180=n+816 | | 4x-2(x-5)=21x-9 | | 9-y=2y | | 17x+36=155 |